The waist width of skis influences the kinematics of the knee joint in Alpine skiing - Zorko, M.; Nemec, B.; Babic, J.; Lesnik, B.; Supej, M. (Journal of Sports Science & Medicine, 2015)
Recently alpine skis with a wider waist width, which medially shifts the contact between the ski edge and the snow while turning, have appeared on the market. The aim of this study was to determine the knee joint kinematics during turning while using skis of different waist widths (65mm, 88mm, 110mm). Six highly skilled skiers performed ten turns on a predefined course (similar to a giant slalom course). The relation of femur and tibia in the sagital, frontal and coronal planes was captured by using an inertial motion capture suit, and Global Navigation Satellite System was used to determine the skiers` trajectories. With respect of the outer ski the knee joint flexion, internal rotation and abduction significantly decreased with the increase of the ski waist width for the greatest part of the ski turn. The greatest abduction with the narrow ski and the greatest external rotation (lowest internal rotation) with the wide ski are probably the reflection of two different strategies of coping the biome-chanical requirements in the ski turn. These changes in knee kinematics were most probably due to an active adaptation of the skier to the changed biomechanical conditions using wider skis. The results indicated that using skis with large waist widths on hard, frozen surfaces could bring the knee joint unfavorably closer to the end of the range of motion in transversal and frontal planes as well as potentially increasing the risk of degenerative knee injuries.